2021
DOI: 10.3390/ijerph18157945
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Dependent Specificities in Cutaneous Melanoma Predisposition, Risk Factors, Somatic Mutations, Prognostic and Predictive Factors: A Systematic Review

Abstract: Background and aim: Over the last decades, the incidence of melanoma has been steadily growing, with 4.2% of the population worldwide affected by cutaneous melanoma (CM) in 2020 and with a higher incidence and mortality in men than in women. We investigated both the risk factors for CM development and the prognostic and predictive factors for survival, stratifying for both sex and gender. Methods: We conducted a systematic review of studies indexed in PUB-MED, EMBASE, and Scopus until 4 February 2021. We inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 107 publications
(112 reference statements)
1
6
0
Order By: Relevance
“…[ 16 ] Our study was based on the median age of previous studies of melanoma, with an age cutoff of 60 years, and demonstrated that ≥ 60 years was a negative predictor of OS and CSS prognosis in patients with SSM, and the results were consistent with the study of Michael et al [ 17 ] Men have a higher incidence of melanoma than women, and women have a higher relative survival rate than men. [ 18 , 19 ] This study also demonstrated lower OS and CSS rates in male patients with SSM, which is consistent with previous studies. Compared with patients of other races, the incidence of SSM in whites was significantly higher than that in other people of color, but the data in this study showed that the number of cases in people of color was very small, and race was not an independent factor in our study.…”
Section: Discussionsupporting
confidence: 92%
“…[ 16 ] Our study was based on the median age of previous studies of melanoma, with an age cutoff of 60 years, and demonstrated that ≥ 60 years was a negative predictor of OS and CSS prognosis in patients with SSM, and the results were consistent with the study of Michael et al [ 17 ] Men have a higher incidence of melanoma than women, and women have a higher relative survival rate than men. [ 18 , 19 ] This study also demonstrated lower OS and CSS rates in male patients with SSM, which is consistent with previous studies. Compared with patients of other races, the incidence of SSM in whites was significantly higher than that in other people of color, but the data in this study showed that the number of cases in people of color was very small, and race was not an independent factor in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Superficial diffusion, nodular, and malignant freckles are the three main histological types of SKCM [ 1 ]. By 2020, 4.2% of the global population suffered from SKCM [ 2 ]. SKCM accounts for about 5% of all skin cancers but more than 2/3 of all skin cancer-related mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The exact cause of melanoma is not yet understood, but there are certain factors that may initiate and promote its development: ultraviolet (UV) radiation, indoor tanning [ 8 , 9 , 10 ], prolonged sun exposure/sunburn [ 11 ], burn scars [ 12 , 13 , 14 ], pesticides, genetic factors/heredity, geographical location, skin phototype, immunosuppression, hormonal changes, a high number of nevi, neuroendocrine factors, stress, depression [ 15 ], trauma, low socioeconomic status, non-melanoma skin cancers, autoimmune diseases, viral infections, biological/cytologic factors, smoking/alcohol, medicines, gender (melanoma has a higher incidence in men [ 16 , 17 , 18 , 19 , 20 ]), etc. [ 1 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%